2020
DOI: 10.1038/s41598-020-62618-3
|View full text |Cite
|
Sign up to set email alerts
|

A multi-institutional real world data study from India of 3453 non-metastatic breast cancer patients undergoing upfront surgery

Abstract: The present analysis reports the clinical, pathological, treatment profile and overall survival (OS) and disease-free survival (DFS) outcomes of consecutive breast cancer patients from three Indian centres, who underwent curative surgery as their first treatment. Among the 3453 patients, stage I, II, and III cases were 11.75%, 66.79%, and 21.64%, respectively while hormone receptor positive/ HER2 negative, triple negative (TNBC) and hormone receptor any/HER2 positive cases were 55.2%, 24.2% and 20.6%, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 26 publications
1
30
0
Order By: Relevance
“…A different molecular subtype was an independent predictive factor for DFS and OS in breast cancer. HER2-positive and triple-negative breast cancers have a poor prognosis compared to other groups (luminal A, luminal B) [16, 17]. In our study it was found that that the molecular subtype was an independent prognostic factor.…”
Section: Discussionsupporting
confidence: 57%
“…A different molecular subtype was an independent predictive factor for DFS and OS in breast cancer. HER2-positive and triple-negative breast cancers have a poor prognosis compared to other groups (luminal A, luminal B) [16, 17]. In our study it was found that that the molecular subtype was an independent prognostic factor.…”
Section: Discussionsupporting
confidence: 57%
“…As per the ICMR data based on cumulative analysis of data from 13 institutions across the country, the cumulative 5-year survival of a cohort of 7609 patients was 73.8%. [ 10 ] Subsequently, there have been a few more studies which have looked at 5-year OS,[ 9 ] which showed better survival, but no Indian data looked at 10-year survival outcome and more. Globally, also there have been only a small number of studies looking at more than 10-year survival outcome from a single hospital.…”
Section: Discussionmentioning
confidence: 99%
“…On literature search, we found a study from India with the largest dataset of breast cancer patients having median follow-up period not more than 6 years; still, around 14% of the total population had lost follow-up within 12 months of surgery. [ 9 ] Since we were looking to document survival statistics of all breast cancer patients treated with a curative intent, we have included patients with bone mets alone and also oligometastatic patients who had a complete response to chemotherapy. We have not included patients who have not taken adjuvant therapy or have gone for alternate medicines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in accordance with other studies. 9,10 We have also attempted to compare our findings with other studies from the Indian subcontinent which have examined TNBC. This is shown in Table 2.…”
mentioning
confidence: 92%